Transformation of Islamic Educational Institution Curriculum to Improve Learning Outcomes in Facing the Challenges of Industrial Society - Sugiannoor; Ilyasin, Mukhamad; Julaiha, Siti (The Indonesian Institute of Science and Technology Research, 2025)
Adapting the curriculum in Islamic educational institutions is crucial in responding to the ever-growing changes in industrial society. This study aims to analyze the strategy of curriculum adaptation in Islamic academic institutions, to prepare competitive graduates while upholding Islamic values. This study uses a descriptive qualitative method with a case study approach at MAN Bontang, SMA Hidayatullah, and SMA Darul Hikmah Boarding School. Data were collected through interviews, observations, and documentation. The study results indicate that curriculum adaptation is carried out through integrating religious knowledge with general knowledge, strengthening industry-based vocational skills, and implementing technology-based and project-based learning methods. Factors driving adaptation include government support, cooperation with the industrial sector, and community demands for Islamic-based education relevant to current developments. However, the main challenges are limited resources, a lack of competent teaching staff in the industrial sector, and resistance to change. This study concludes that effective curriculum adaptation can increase the competitiveness of graduates of Islamic educational institutions in the world of work while maintaining Islamic identity.